Microstructure and mechanical properties of Si3N4f/Si3N4 composites with different coatings. Issue 10 (July 2019) - Zhou, Jie; Ye, Fang; Cheng, Laifei; Li, Mingxing; Yue, Wei; Wang, Yusheng
Abstract: The Si3 N4 coating and Si3 N4 coating with Si3 N4 whiskers as reinforcement (Si3 N4w -Si3 N4 ) were prepared by chemical vapor deposition (CVD) on two-dimensional silicon nitride fiber reinforced silicon nitride ceramic matrix composites (2D Si3 N4f /Si3 N4 composites). The effects of process parameters of as-prepared coating including the preparation temperature and volume fraction of Si3 N4w on the microstructure and mechanical properties of the composites were investigated. Compared with Si3 N4 coating, Si3 N4w -Si3 N4 coating shows more significant effect on the strength and toughness of the composites, and both strengthening and toughening mechanism were analyzed.